(untitled) (Scientia Agricola, 2013)
Strategies to mitigate climate change through the use of biofuels (such as ethanol) are associated not only to the increase in the amount of C stored in soils but also to the reduction of GHG emissions to the atmosphere.This report mainly aimed to propose appropriate methodologies for the determinations of soil organic carbon stocks and greenhouse gas fluxes in agricultural phase of the sugarcane production. Therefore, the text is a piece of contribution that may help to obtain data not only on soil carbon stocks but also on greenhouse gas emissions in order to provide an accurate life cycle assessment for the ethanol. Given that the greenhouse gas value is the primary measure of biofuel product quality, biorefiners that can show a higher offset of their product will have an advantage in the market place.